Pemanfaatan Teknologi Informasi dan Komunikasi dalam Pembelajaran di SMA Bayt al-Hikmah Pasuruan - Fitri Kurnia (Tarbawi : Jurnal Studi Pendidikan Islami, 2023)
The needs and lifestyle of society in the current era have given rise to developments in various fields, one of which is technology. Changes in learning patterns are needed to carry out updates to keep up with the dynamics of increasingly rapid changes triggered by technological developments. This research uses a qualitative approach with a descriptive model to analyze and explain how information and communication technology is used in learning at SMA Bayt Al-Hikmah Pasuruan. Based on the research conducted, it can be said that the teacher paradigm when utilizing information and communication technology in learning is still limited to the use of presentations, especially power points. The use of the internet is still limited to searching for information about the material that will be presented rather than being used as a new integrated learning system, likewise social networking is still not widely used as a new learning system to further increase the effectiveness and efficiency of the learning process.